Influência do nível de bateria de unidade led de amplo espectro na transmitância e grau de conversão de cimento resinoso fotoativado sob diferentes espessuras / translucidez cerâmicas - Azevedo, Michele Ramos de (2018)
Objectives: This study aimed to evaluate the influence of battery level of a broad spectrum LED unit on transmittance and degree of conversion of a light-cure resin cement with alternative photoinitiators activated under different lithium disilicate ceramic thicknesses and translucency. The wavelenghts delivered by the LED curing unit under the different conditions were also determinated. Methods and Materials: Forty lithium disilicate ceramic discs of high and low translucency (IPS e.max Press HT and LT, shade A1), 12 mm in diameter with variable thickness (0.5 mm, 1.0 mm, 1.5mm, and 2.0 mm) were produced and divided into the experimental groups according to the ceramic thickness and translucency (n=5). Resin cement specimens (Variolink Esthetic LC, Neutral), with 3,9 mm of diameter and 1,0mm of thickness, were obtained for each ceramic thickness and translucency under the different battery levels (100%, 50%, 10%) of the broad spectrum LED curing unit (BluePhase G2). The analysis of the transmittance (T) and wavelengths (W) delivered by the LED unit at the different conditions were determined using a USB4000 spectrometer referenced by NIST, MARC (Bluelight Analytics Inc., Halifax, Canada). After storing specimens for 24 h, the degree of conversion (DC) of the resin cement photoactivated under the different conditions was evaluated using FTIR. After checking for homocedasticity, data were submitted to three-way analysis of variance, followed by Tukey HSD test (α=0.05). Results: No significant interaction was detected for battery level x thickness at HT translucency (P = 0.265), but at LT translucency it was significant (P <0.001). Significant differences were found for transmittance on HT specimens between 100% and 10% battery levels (P <0.001), but it was not significant between 100% and 50% (P = 0.085) and 50% and 10% (P = 0.170) battery levels. Significant differences among the different ceramic thickness were verified for HT specimens (P <0.001). Differences were observed on LT specimens between 100% and 10% (P <0,001), 50% and 10% (P <0,001), but not for 100% and 50% (P = 0,994). Transmittance values among battery levels was not significantly different within LT 2.0 mm (P = 0.125), 1.5 mm (P = 0.326), and 1.0 mm (P = 0.007) groups, but for the values of LT 0.5 mm group were significantly different - 4 - (P <0.001). Significant differences were detected for all LT thickness evaluated within 100% (P <0,001), 50% (P <0,001), 10% (P <0,001) battery levels. At 10% battery level, the LT 0,5 mm group showed similar transmittance to LT 1,0mm group (P= 0,599). The DC values were significantly different among battery levels (P = 0,002), but no significant differences were found for DC among the different ceramic thickness (P = 0,328) neither among the translucency (P = 0,650). Conclusions: Lower battery levels influenced the broad spectrum LED unit transmittance and consequently the degree of conversion of the resin cement in the different ceramic thicknesses and translucency. The amount of light transmitted through ceramic restorations can be gradually reduced by ceramic restorations with increased thickness/ translucency, irrespective of the LED unit battery levels.